2016
DOI: 10.1016/j.jpor.2015.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of clasp design and flexural properties of acrylic denture base materials for use in non-metal clasp dentures

Abstract: The results thus suggested that some of the acrylic materials used as denture base materials may also be usable for NMCDs, and that the flexural properties of the acrylic material PI resemble those of ES, ESB and ACT, meaning that similar clasp designs may also be feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…Hamanaka et al also reported relatively low flexural properties of thermoplastic resins at the proportional limit (PL) point 16,17) . There have been other reports demonstrating higher flexural strength of thermoplastic resins [18][19][20] . Cumulatively, there are substantial differences or conflicts in the reported mechanical properties within the literature data and between the literature and manufacturer data 8) .…”
Section: Introductionmentioning
confidence: 92%
“…Hamanaka et al also reported relatively low flexural properties of thermoplastic resins at the proportional limit (PL) point 16,17) . There have been other reports demonstrating higher flexural strength of thermoplastic resins [18][19][20] . Cumulatively, there are substantial differences or conflicts in the reported mechanical properties within the literature data and between the literature and manufacturer data 8) .…”
Section: Introductionmentioning
confidence: 92%
“…However, extensive studies are necessary in order to understand the interactions between the CNF and the acrylic resin interface. The mechanical evaluation of denture base materials frequently involves the determination of flexural properties 28) ; numerous studies have examined the flexural properties of denture base resins 29,30) . Water molecules can penetrate a polymer structure and act as a plasticizer, leading to a reduction in the mechanical properties of the structure 31) .…”
Section: Discussionmentioning
confidence: 99%
“…The increase in curing temperature was reported to yield pore-free structures and low levels of residual monomer associated with low water absorption [11]. NMCD materials such as polyamide, polyester or polycarbonate showed better fracture- and impact-resistance than acrylic materials, but they were difficult to grind, had low color stability, and needed short span maintenance [12]. Therefore, extensive research was carried out to improve the properties of acrylic denture base materials by mixing PMMA with suitable fillers.…”
Section: Introductionmentioning
confidence: 99%